A Molecular Hybrid of an Atomically Precise Silver Nanocluster and Polyoxometalates for H2 Cleavage into Protons and Electrons. Issue 31 (26th June 2021) - Yonesato, Kentaro; Yamazoe, Seiji; Yokogawa, Daisuke; Yamaguchi, Kazuya; Suzuki, Kosuke
Abstract: Atomically precise silver (Ag) nanoclusters are promising materials as catalysts, photocatalysts, and sensors because of their unique structures and mixed‐valence states (Ag + /Ag 0 ). However, their low stability hinders the in‐depth study of their intrinsic reactivity and catalytic property accompanying their redox processes. Herein, we demonstrate that a molecular hybrid of an atomically precise Ag27 17+ nanocluster and polyoxometalates (POMs) can efficiently cleave H2 into protons and electrons. The Ag nanocluster accommodates electrons through the redox reaction from Ag27 17+ to Ag27 13+, and the POM ligands play the following important roles: (i) a significant stabilization of the typically unstable Ag nanocluster to preserve its structure during the redox reaction with H2, (ii) formation of a unique interface between the Ag nanocluster and metal oxides for efficient H2 cleavage, and (iii) storage of the generated protons on the negatively charged basic surface. Abstract : A molecular hybrid of an atomically precise mixed‐valent Ag27 17+ nanocluster and polyoxometalate (POM) ligands exhibited unique reactivity, efficiently cleaving dihydrogen (H2 ) into protons and electrons. The protons and electrons generated are stored on the POM surface and the mixed‐valent Ag27 17+ nanoclusters, respectively.